Aplicação de inoculante no plantio e doses de adubação nitrogenada de cobertura na cultura do feijoeiro (Phaseolus vulgaris) - Nyssen, Diego (Universidade Federal de São Carlos, 2016)
The bean crop has the great challenge of increasing productivity and reducing dependence on nitrogen (N) fertilization from biological N fixation, aiming at a sustainable development of agriculture. The objective of this work was to evaluate the productivity, biometric parameters, and N absorption in the bean crop with or without the application of inoculant at planting and with the supply of different doses of N in coverage. The experiment was carried out in the experimental area at the UFSCar Center for Agricultural Sciences, in a completely randomized design with five replications, consisting of two factors: with and without the addition of biological binoculant at planting; five doses of N top-dressing fertilization (0, 50, 75, 100, and 150% of the recommended dose by the Agronomic Institute of Campinas). After 25 days of plant emergence, top-dressing fertilization was carried out and 48 days after emergence, leaves were sampled for foliar analysis. The parameters evaluated in the experiment were: phytomass, number of pods per plant, number of grains per pod, length of pods, mass of 100 seeds, production and productivity of the plot, and levels of foliar N. The lack of response of several biometric parameters to biological inoculation and to the top-dressing N fertilization was attributed to the current fertility of the experimental area (scenario of low response to N). However, the addition of inoculant at planting, with top-dressing N fertilization equivalent to 150% of the recommended amount, resulted in a significant increase in yield, foliar N contente, and number of pods per plant. Seed inoculation was considered an indispensable practice, but it is possible that the top-dressing N fertilization doses, recommended for the edaphoclimatic conditions of the State of São Paulo, are being insufficient for the maximum expression of the currently cultivated bean varieties.
Biological inoculation at planting and top-dressing nitrogen fertilization rates in bean crop (Phaseolus vulgaris)
Keywords: Feijoeiro-comum; Fixação biológica de nitrogênio; FBN; Bean crop; Top-dressing fertilization; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO